BERAT POTONG AYAM BROILER YANG DIBERI EKSTRAK KUNYIT PUTIH (Curcuma zedoaria) DENGAN DOSIS YANG BERBEDA SECARA ORAL - Tuarita, Hejer; Ralahalu, Tabita naomi; Patty, Christian (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This research was conducted to determine the effect of oral administration of white turmeric extract (Curcuma Zedoaria) at different levels on the slaughter weight of broiler chickens. This research will take place for 3 months, August – October 2023 at the Faculty of Agriculture, Department of Animal Husbandry, Livestock Unit, Pattimura University, Ambon. Completely Randomized Design (CRD) was used in this study with 4 replications and 4 treatments, the replications consisted of 6 chickens.  The treatments applied were P0 = feed without giving turmeric extract (control), P1= feed + turmeric extract 0.7 ml/head, P2= feed + turmeric extract 1.4 ml/head, P3= feed + turmeric extract 2.1 ml /tail. The variables observed were feed consumption and slaughter weight.  The results of the research conducted showed that oral administration of white turmeric extract had no significant effect (P > 0.05) on feed consumption and slaughter weight of broiler chickens. However, numerically the administration of white turmeric extract resulted in a higher increase in the slaughter weight of broiler chickens compared to the slaughter weight of broiler chickens without the administration of white turmeric extract.